The whole at a glance: risk, information and corporate decisions. (2015) - Corelli, Angelo
The paper aims to be a guide for understanding the role of information in decision making and how this influences the decisions regarding financing a corporation. The risk approach is widely used in practice in order to establish precise boundaries in which decision plans can be constrained in order to optimise the outcome of the funding process. That is in the interest of the shareholders but also external investors who might be interested in joining determined projects. Finally, the Appendix describes in details the delta normal approach as a good value at risk methodology to assess risk.